Analisis Perceived Enjoyment Dan Perceived Ease Of Use Untuk Pembayaran Digital Menggunakan Layanan Gopay Pada Masyarakat di Bandar Lampung - Sivia Nurma Ayu; Fatih Fuadi; Ahmad Hazas Syarif (CV. Ulil Albab Corp, 2025)
This study examines the influence of perceived enjoyment and perceived ease of use on the adoption of GoPay digital payment services in Bandar Lampung, Indonesia. Using a qualitative case study approach, the research involved 20 active GoPay users from diverse demographic backgrounds, with data collected through in-depth interviews, participant observation, and focus group discussions. The findings reveal that perceived enjoyment significantly influences GoPay adoption, with an average score of 4.65 out of 5, indicating users' highly positive experiences with the service. Similarly, perceived ease of use demonstrates a substantial impact, achieving an average score of 4.77, reflecting the platform's user-friendly interface and efficient transaction process. The study identifies a strong positive correlation (r=0.893) between these two factors, contributing to an impressive 89% adoption rate among Bandar Lampung residents. The research also highlights GoPay's success in creating an effective digital payment ecosystem, evidenced by a 92% user satisfaction rate and average transaction times under 10 seconds. Furthermore, the study shows that GoPay's reward system and intuitive interface have successfully fostered user engagement and loyalty. These findings contribute to the understanding of digital payment adoption in medium-sized Indonesian cities and provide valuable insights for financial technology service providers and policymakers in developing inclusive digital payment ecosystems.